Experimental investigation of energy storage properties and thermal conductivity of a novel organic phase change material/MXene as A new class of nanocomposites. (February 2020) - Aslfattahi, Navid; Saidur, R.; Arifutzzaman, A.; Sadri, R.; Bimbo, Nuno; Sabri, Mohd Faizul Mohd; Maughan, Philip A; Bouscarrat, Luc; Dawson, Richard J.; Said, Suhana Mohd; Goh, Boon Tong; Sidik, Nor Azwadi Che
Highlights: novel formulation (PCM/MXene) as a novel composite with enhanced properties. Synthesizing a new class of nanocomposites. Increment of specific heat capacity of nanocomposites compared with pure PCM. Increment of thermal conductivity of nanocomposites. Improved thermal stability of synthesized nanocomposites. Abstract: Energy storage is a global critical issue and important area of research as most of the renewable sources of energy are intermittent. In this research work, recently emerged inorganic nanomaterial (MXene) is used for the first time with paraffin wax as a phase change material (PCM) to improve its thermo-physical properties. This paper focuses on preparation, characterization, thermal properties and thermal stability of new class of nanocomposites induced with MXene nanoparticles in three different concentrations. Acquired absorbance (UV-Vis) for nanocomposite with loading concentration of 0.3 wt.% of MXene achieved 39% enhancement in comparison with the pure paraffin wax. Thermal conductivity measurement for nanocomposites in a solid state is performed using a KD2 PRO decagon. The specific heat capacity ( c p ) of PCM based MXene is improved by introducing MXene. The improvement of c p is found to be 43% with 0.3 wt.% of MXene loaded in PCM. The highest thermal conductivity increment is found to be 16% at 0.3 wt.% concentration of MXene in PCM. Decomposition temperature of this new class of nanocomposite with 0.3 wt.% mass fraction is increased by 6%. This improvement is beneficial in thermal energy storage and heat transfer applications. Graphical Abstract: Image, graphical abstract